1995
DOI: 10.1002/pen.760352105
|View full text |Cite
|
Sign up to set email alerts
|

Mixing and morphological transformations in the compounding process for polymer blends: The phase inversion mechanism

Abstract: This study reports on the progression of processes occurring in polymer blends during mixing. For the polymer pellet blends studied, an abrupt phase inversion was observed simultaneous with attainment of maximum torque in the batch mixer. A four‐step phase inversion mechanism is described as predominant where dissipative mix‐melting of the polymer system occurred in the mixing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 13 publications
3
24
0
Order By: Relevance
“…As a result, the average domain size and the average distance of the interdomains reach a steady value. Changes in parameters with the blending time are similar with those provided in references, [8][9][10][11][12][13] but a slight difference between the results and the references [8][9][10][11][12][13] lies in the temporally different starting point at the initial stage of blending. These parameters can represent the temporal evolution of the phase morphology and the dynamics in a way.…”
Section: Evolution Of Phase Morphology By Pcmsupporting
confidence: 73%
See 1 more Smart Citation
“…As a result, the average domain size and the average distance of the interdomains reach a steady value. Changes in parameters with the blending time are similar with those provided in references, [8][9][10][11][12][13] but a slight difference between the results and the references [8][9][10][11][12][13] lies in the temporally different starting point at the initial stage of blending. These parameters can represent the temporal evolution of the phase morphology and the dynamics in a way.…”
Section: Evolution Of Phase Morphology By Pcmsupporting
confidence: 73%
“…[1][2][3][4][5][6][7][8] To monitor the phase formation and evolution in time, some smart researchers have studied changes of the phase morphology during the mixing and found that the changes of phase morphology occur within the first 2 min. [8][9][10][11][12][13] During the mixing, the phase dimension size decreases promptly at the initial stage. Here, the breakup of domains is preferential because of the shear effect.…”
Section: Introductionmentioning
confidence: 99%
“…The deviation from the Ozawa equation for the nonisothermal crystallization of iPB-1/Mult920 may be due to the crystallization processing being in different periods for different cooling rates at a given temperature. Combining the Avrami equation and the Ozawa equation, a new approach was developed by Mo [13] to describe the kinetics of nonisothermal crystallization. For a given nonisothermal crystallization process, comparing Equations (3) and (5), the following equation is obtained:…”
Section: Nonisothermal Crystallization Kinetic Analysismentioning
confidence: 99%
“…[1 -24] For instance, Favis [4] studied the mixing process using an intermittent mixer and found the change of the phase morphology occurred mainly within the first 2 min Scott et al [13] investigated the phase transformation in the initial stage of the blending process using an intermittent mixer, single-screw extruder and twin-screw extruder, respectively and came to a similar conclusion. To monitor the phase formation and evolution with time, Shih [14] opened a window on the mixer and observed the macroscopic structure change, using a vidicon.…”
Section: Introductionmentioning
confidence: 99%